2022
DOI: 10.3390/biomedicines10051049
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Secreted Factors from Dental Pulp Stem Cells for Various Diseases

Abstract: An alternative source of mesenchymal stem cells has recently been discovered: dental pulp stem cells (DPSCs), including deciduous teeth, which can thus comprise potential tools for regenerative medicine. DPSCs derive from the neural crest and are normally implicated in dentin homeostasis. The clinical application of mesenchymal stem cells (MSCs) involving DPSCs contains various limitations, such as high cost, low safety, and cell handling issues, as well as invasive sample collection procedures. Although MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 161 publications
0
7
0
Order By: Relevance
“…The paracrine effects of DPSCs have been highlighted in regenerative medicine. It has been reported that DPSCs can secrete many bioactive molecules such as interleukin (IL)-10, IL-13, follistatin, transforming growth factor-β1, hepatocyte growth factor, neural cell adhesion molecule-1, and adiponectin ( Ogata et al, 2021 ; Ogata et al, 2022 ). The bioactive molecules secreted by DPSCs can directly affect their own intracellular signal transduction, and can also indirectly cause neighboring cells to secrete functional active substances ( Mattei et al, 2021 ).…”
Section: The Potential Mechanisms Of Dpscs In Scimentioning
confidence: 99%
“…The paracrine effects of DPSCs have been highlighted in regenerative medicine. It has been reported that DPSCs can secrete many bioactive molecules such as interleukin (IL)-10, IL-13, follistatin, transforming growth factor-β1, hepatocyte growth factor, neural cell adhesion molecule-1, and adiponectin ( Ogata et al, 2021 ; Ogata et al, 2022 ). The bioactive molecules secreted by DPSCs can directly affect their own intracellular signal transduction, and can also indirectly cause neighboring cells to secrete functional active substances ( Mattei et al, 2021 ).…”
Section: The Potential Mechanisms Of Dpscs In Scimentioning
confidence: 99%
“…9 As neural crest-derived cells, DPSCs can be used for cell therapy along several cell lineages. 51 Currently, many studies have demonstrated the ability of DPSCs in neural differentiation, angiogenesis, dentinogenesis, osteogenesis, and chondrogenesis, 41,42,[52][53][54][55][56] not only in the maxillofacial region but also in tissues throughout the body (eg, the brain, heart, cornea). Recently, their secreted factors have shown therapeutic potential in various diseases.…”
Section: Dental-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Interestingly, some studies also suggested the superiority of the secretome obtained from DSCs compared to other MSCs sources, such as BM-MSCs and adipose-derived mesenchymal stem cells (AD-MSCs), for neuroprotection [ 121 ]. The secreted factors can be found in the cell culture medium called Conditioned Medium (CM) and in the Exosomes (Exos) they secrete [ 122 ], representing an attractive, noninvasive, and acellular tool for therapeutic approaches against various disorders [ 123 ]. A summary of the main factors found in the DSCs’ secretome is given in Table 2 .…”
Section: Dscs Secretomementioning
confidence: 99%